2010
DOI: 10.1186/1465-9921-11-164
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neutral endopeptidase activity during clinical and experimental acute lung injury

Abstract: BackgroundNeutral endopeptidase (NEP), an enzyme that cleaves inflammatory bioactive peptides, may play a protective role in the pathogenesis of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). However, its low extracellular activity hinders the precise measurement of changes that take place during ALI/ARDS. The main objective of this study was to clarify the regulation of NEP activity and its expression during ALI/ARDS.MethodsIn a clinical study, we measured plasma NEP activity in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…NEP is a membrane bound zinc metallopeptidase responsible for the metabolism and inactivation of an array of vasodilator (e.g., natriuretic peptides, adrenomedullin, vasoactive intestinal peptide) and vasoconstrictor (e.g., angiotensin II, endothelin-1 [ET-1]) peptides (Erdos & Skidgel, 1989;Kenny & Stephenson, 1988). These observations fit with the up-regulation of NEP in the pulmonary circulation during acute lung injury and heart failure (Abassi, Kotob, Golomb, Pieruzzi, & Keiser, 1995;Hashimoto, Amaya, Oh-Hashi, Kiuchi, & Hashimoto, 2010). These observations fit with the up-regulation of NEP in the pulmonary circulation during acute lung injury and heart failure (Abassi, Kotob, Golomb, Pieruzzi, & Keiser, 1995;Hashimoto, Amaya, Oh-Hashi, Kiuchi, & Hashimoto, 2010).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…NEP is a membrane bound zinc metallopeptidase responsible for the metabolism and inactivation of an array of vasodilator (e.g., natriuretic peptides, adrenomedullin, vasoactive intestinal peptide) and vasoconstrictor (e.g., angiotensin II, endothelin-1 [ET-1]) peptides (Erdos & Skidgel, 1989;Kenny & Stephenson, 1988). These observations fit with the up-regulation of NEP in the pulmonary circulation during acute lung injury and heart failure (Abassi, Kotob, Golomb, Pieruzzi, & Keiser, 1995;Hashimoto, Amaya, Oh-Hashi, Kiuchi, & Hashimoto, 2010). These observations fit with the up-regulation of NEP in the pulmonary circulation during acute lung injury and heart failure (Abassi, Kotob, Golomb, Pieruzzi, & Keiser, 1995;Hashimoto, Amaya, Oh-Hashi, Kiuchi, & Hashimoto, 2010).…”
Section: Introductionmentioning
confidence: 68%
“…Indeed, preclinical evidence indicates that NEP −/− mice are less susceptible to hypoxiainduced pulmonary oedema (Irwin, Patot, Tucker, & Bowen, 2005) and that inhibition of NEP attenuates hypoxia-induced PH by potentiating the action of natriuretic peptides Thompson, Sheedy, & Morice, 1994;Winter, Zhao, Krausz, & Hughes, 1991). These observations fit with the up-regulation of NEP in the pulmonary circulation during acute lung injury and heart failure (Abassi, Kotob, Golomb, Pieruzzi, & Keiser, 1995;Hashimoto, Amaya, Oh-Hashi, Kiuchi, & Hashimoto, 2010).…”
Section: Introductionmentioning
confidence: 80%
“…In an experimental and clinical study of ARDS, the activity of NEP was significantly increased in the alveolar air space, thereby suggesting a pivotal role of this enzyme in acute lung injury [ 66 ]. In fact, it has been demonstrated that several cytokines, including IL-1α, TNF-α, transforming growth factor, IL-6, and granulocyte macrophage colony-stimulating factor, enhance activity of NEP on the surface of intact lung fibroblasts [ 67 ].…”
Section: Rationale For Angiotensin Receptor Neprilysin Inhibition mentioning
confidence: 99%
“…In ammation causes disease through uid transfer across cell membranes and cell layers, which leads to changes in muscle function and pain, and changes in ion channels have been detected in ALI [39]. Neutral endopeptidase is an enzyme that cleaves in ammatory bioactive peptides and plays a protective role in the pathogeneses of ALI and ARDS [40].…”
Section: Discussionmentioning
confidence: 99%